An investigation into the presentation of trauma in adolescents with a developmental disability and psychological treatment of trauma in adolescents - Morris, Donna (2015)
This thesis provides an investigation into the presentation and treatment of childhood maltreatment in adolescents, with a key focus on adolescents with developmental disabilities (DD). A range of methods, including an empirical study, a systematic review, a single case study and a critical evaluation of a psychometric assessment were used to explore this field. The empirical study explores the presentation of childhood maltreatment in a cohort of adolescents with and without DD, within a specialist inpatient setting. The systematic review investigates the effectiveness of psychological treatments for adolescents with a history of childhood maltreatment. The case study explores the effectiveness of an Adapted Sex Offender Treatment Programme (ASOTP) at reducing the risk of sexual re-offending, for a male adolescent with DD and a history of childhood maltreatment. The critical evaluation of the Trauma Symptom Checklist for Children (TSCC) (Briere, 1996) focuses on evaluating the reliability, validity and applicability of the measure for use with adolescents in secure psychiatric settings. The preliminary results of the empirical study found no significant differences between both groups for the dependent measures, however data trends suggested that adolescents with DD display a higher frequency of problematic behaviours. They also displayed some trauma symptoms and emotions more frequently compared with adolescents without DD. The findings of the systematic review were unclear due to methodological issues and bias, however the review showed that Cognitive Behavioural Therapy was not effective at reducing depression but Attachment Based Family Therapy may be an effective intervention for reducing depression and suicidal ideation in adolescents. The case study found that the ASOTP was not effective at reducing the Client’s risk of re-offending. The Client did not engage well with the work and the reasons for this are discussed in relation to the Client’s history of maltreatment and development of personality disorder traits. In the critical evaluation of the TSCC, it is recognised that the TSCC is a strong measure of trauma, however it has not been validated or standardised for use with children/adolescents with DD. The thesis concludes that there are many avenues of research about maltreated adolescents with DD which need to be explored. This research field needs to be substantially developed before clinicians can reap the beneficial clinical implications of the research.